Penegakan Hukum Terhadap Pelaku Perbuatan Main Hakim Sendiri (Studi di Wilayah Hukum Kepolisian Resor Semarang Barat) - Aprisylia Dwi Hapsari, Rochmani (Jurnal Ilmiah Dinamika Hukum, 2019)
Vigilantism itself is an offense that still often occurs in the community around us. This violates the provisions of article 170 paragraph (1) and (2) of the Criminal Code, article 351 paragraph (2) and (3) of the Criminal Code, article 354 paragraph (1) and (2) of the Criminal Code. Violations of vigilantism are not justified because it is as if the community as the perpetrators of vigilantism ignores the legal process in force in Indonesia. Then there needs to be protection for the suspect or victim of vigilantism even though he is a criminal. It aims to achieve justice and legal processes in this country. The formulation of the problem of this research is What are the factors - factors that cause the occurrence of vigilante actions, How is law enforcement against perpetrators of vigilante acts (Study in the Legal Area of ​​the West Semarang District Police). The type of research used in this study is juridical normative. The research specifications are analytical descriptive. This study uses two sources of cracked data: primary data and secondary data. The method of presenting data in research is done in a descriptive way. The analysis used in writing this thesis is qualitative. The results showed that, the factors that caused the act of vigilantism were spontaneous arising from a group of people who came from social pressure factors, lack of public trust in law enforcement officials, lack of knowledge of people who conduct vigilante about the law and busy people capture the moment of vigilante with a cellphone rather than having to break up. Law enforcement against perpetrators of vigilante conduct (Studies in the Legal Area of ​​the West Semarang District Police) by conducting, overcoming, and minimizing the occurrence of vigilante acts both from the policy of penal policy (repressive) in accordance with article 27 paragraph (1) of the 1945 Constitution, article 170 paragraph (1) and (2) KUHP, article 351 paragraph (2) and (3) KUHP, article 338 KUHP article 354 paragraph (1) and (2) as well as non-penal (preventive) is done by conducting counseling to the community in the area - areas considered to be the scene of vigilantism and carrying out routine patrols. Keywords: Factors, Enforcement, Self-Performing Judges.